Sustainable Diets in Southeast Asia: Development, Barriers, and Opportunities - Tri Fajarwaty; Ahmad Syafiq; Ikeu Tanziha; Siti Khodijah Parinduri (Epidemiology and Society Health Review (ESHR), 2025)
Background: Southeast Asia is experiencing a dietary shift from traditional plant-based diets to Westernized, processed foods, contributing to rising non-communicable diseases and environmental degradation. Given the significant impact of global food production on greenhouse gas emissions, freshwater consumption, and biodiversity loss, promoting sustainable diets in Southeast Asia is critical. This review aims to explore the current progress, barriers, and opportunities in adopting sustainable diets across the region. Method: A scoping review was conducted using a systematic framework to map the existing literature on sustainable diets in Southeast Asia. A total of 37 studies were identified and analyzed to understand the progress, barriers, and opportunities in adopting sustainable diets. Results: The review shows varying levels of progress across Southeast Asia, with countries like Indonesia and Malaysia advancing through government policies and sustainable agriculture practices. However, economic, cultural, and infrastructural barriers hinder broader adoption. Promising opportunities include leveraging alternative protein sources and the region’s biodiversity. Conclusion: While Southeast Asia has substantial potential for implementing sustainable diets, overcoming economic, cultural, and infrastructural challenges will require coordinated efforts between governments, stakeholders, and communities. Collaborative action is necessary to promote food systems that benefit public health and the environment.